Virtual drug testing: redefining sample collection in a global pandemic - Fedoruk, M. N. (Bioanalysis, 2020)
Protecting the integrity of sport & the doping control process The recent global COVID-19 pandemic is an unprecedented global health crisis with far-reaching impacts on sport. With world sporting events canceled or postponed to limit the spread of infectious disease among athletes and the public and athletes adapting their training programs within the safety and protection of their own homes, global anti-doping programs face the challenge of protecting the health and wellbeing of athletes and sample collection personnel while continuing to pursue the detection and deterrence value of anti-doping testing programs. These uncertain and exceptional circumstances require innovation and flexibility within the current anti-doping system to protect the rights of clean athletes and the integrity of sport.